Anisotropic point defects in rhenium diselenide monolayers - Zhu, Yong (2023)
Point defects in 1T″ anisotropic ReSe2 offer many possibilities for defect engineering, which could endow this two-dimensional semiconductor with new functionalities, but have so far received limited attention. Here, we systematically investigate a full spectrum of point defects in ReSe2, including vacancies (VSe1-4), isoelectronic substitutions (OSe1-4 and SSe1-4), and antisite defects (SeRe1-2 and ReSe1-4), by atomic-scale electron microscopy imaging and density functional theory (DFT) calculations. Statistical counting reveals a diverse density of various point defects, which are further elaborated by the formation energy calculations. Se vacancy dynamics was unraveled by in-situ electron beam irradiation. DFT calculations reveal that vacancies at Se sites notably introduce in-gap states, which are largely quenched upon isoelectronic substitutions (O and S), whereas antisite defects introduce localized magnetic moments. These results provide atomic-scale insight of atomic defects in 1T″-ReSe2, paving the way for tuning the electronic structure of anisotropic ReSe2 via defect engineering.